The law of diminishing returns: woodland birds respond to native vegetation cover at multiple spatial scales and over time. Issue 1 (9th November 2013) - Cunningham, Ross B.; Lindenmayer, David B.; Crane, Mason; Michael, Damian R.; Barton, Philip S.; Gibbons, Philip; Okada, Sachiko; Ikin, Karen; Stein, John A. R.; Heikkinen, Risto
Abstract Aim To quantify at multiple spatial scales: (1) spatial dependence in several measures of aggregate bird biodiversity, (2) the role of native vegetation cover in explaining variation in aggregate bird biodiversity and (3) relationships between change over 8 years in bird diversity and changes in native vegetation. Location South‐eastern Australia. Methods We gathered data on birds between 2002 and 2010 on 184 (2 ha) sites nested within 46 (1000 ha) farms nested within 23 (10, 000 ha) landscapes. We statistically estimated spatial and temporal components of variation at the landscape, farm and site scale for several composite indices of bird diversity. Second, we modelled the relationships between aggregate bird biodiversity and log % of native vegetation cover at each spatial scale and over time. Results Variation in bird biodiversity at the landscape, farm and site scale exhibited significant, intrinsic scale‐specific effects. This dependence was largely accounted for by native vegetation cover with aggregate biodiversity increasing with increasing native vegetation cover at each spatial scale and over time. Every doubling of % cover resulted in an increase of 3.1, 2.3 and 0.7 species per landscape, farm and site, respectively. Similar statistically significant positive relationship between proxy abundance and richness of species of conservation concern and % cover of vegetation were also found. Species richness at the site scale also was related to vegetation cover in the surrounding landscape. Over the period of study, relationships between changes in bird biodiversity and changes in vegetation cover were not statistically significant. Main conclusions We used 'diminishing returns' response curves to model relationships between measures of bird biodiversity and vegetation cover at all spatial scales. Absolute gains in biodiversity per unit increase in vegetation cover were greatest at relatively low amounts of vegetation cover. These results can help prioritize investment strategies such as replanting native vegetation under agri‐environment schemes.